VIGABATRIN TOXICITY IN INFANCY IS ASSOCIATED WITH RETINAL DEFECT IN ADOLESCENCE: A Prospective Observational Study. Issue 5 (May 2017) - Wright, Tom; Kumarappah, Ananthavalli; Stavropoulos, Aphrodite; Reginald, Arun; Buncic, J. Raymond; Westall, Carol A.
Abstract : Purpose: The purpose was to determine whether vigabatrin (VGB) (Sabril)-attributed retinal toxicity defined by electroretinogram in early childhood is associated with visual system defect in adolescents after discontinuation of VGB. Methods: This prospective cross-sectional study included 24 children previously treated with VGB and monitored in early childhood by electroretinogram for VGB-attributed retinal defects. Ten had been diagnosed with VGB-attributed retinal defect (Group I) and 14 had no VGB-attributed retinal defect (Group II). Outcome measures were extent of monocular visual fields using Goldmann kinetic perimetry and RNFL thickness at the optic nerve head, using optical coherence tomography. Results: Of those able to complete testing (6 eyes Group I and 16 eyes Group II), Goldmann results revealed results of visual field loss in Group I and not in Group II. The optical coherence tomography results demonstrated attenuation of the RNFL in all 6 eyes of Group I participants and in only 1 eye of 10 Group II participants. Optical coherence tomography data were nonoverlapping between Group 1 and Group II eyes. Conclusion: The VGB-attributed retinal toxicity identified by means of electroretinogram in infancy was associated with visual field loss and RNFL attenuation of the retinal nerve when tested in adolescence. Abstract : Supplemental Digital Content is Available in the Text.Vigabatrin-attributed retinal toxicity diagnosed in infancy by electroretinogram was associated with Goldmann visual fields and optical coherence tomography retinal nerve fiber layer defect in adolescence. The importance of optical coherence tomography monitoring was highlighted by the lack of overlap between retinal nerve fiber layer data from those previously identified with and without retinal toxicity.